Spontaneous resolution of acute gouty arthritis is associated with rapid induction of the anti-inflammatory factors TGFβ1, IL-10 and soluble TNF receptors and the intracellular cytokine negative regulators CIS and SOCS3. Issue 9 (25th May 2011) - Chen, Yu-Hsuan; Hsieh, Song-Chou; Chen, Wei-Yu; Li, Ko-Jen; Wu, Cheng-Han; Wu, Po-Chang; Tsai, Chang-Youh; Yu, Chia-Li
Abstract : Objective: The molecular basis for spontaneous resolution of acute gouty arthritis (GA) remains unclear. The hypothesis that extracellular and intracellular mechanisms play roles in resolving acute GA was tested. Methods: Synovial fluid (SF) levels of transforming growth factor β1 (TGFβ1), interleukin 1 (IL-1) receptor antagonist (IL-1ra), IL-10 and soluble tumour necrosis factor (TNF) receptor I (sTNFRI) and II (sTNFRII) were measured by ELISA in patients with acute GA and osteoarthritis (OA). Monosodium urate (MSU) crystal-stimulated RAW264.7 mouse macrophages were analysed for cytokine inducible SH2-containing protein (CIS) and suppressors of cytokine signalling (SOCS)1-7 mRNA expression by reverse transcription (RT)-PCR. Immunohistochemical analysis, quantitative PCR and immunoblotting were performed to detect CIS and SOCS3 expression in synovial tissue, SF mononuclear cells (SFMCs) from patients with GA and MSU crystal-stimulated monocyte-derived macrophages from healthy donors. CIS overexpression and small interfering RNA-mediated knockdown in RAW264.7 cells were used to investigate the role of CIS in resolving MSU crystal-induced acute inflammation. Results: SF levels of anti-inflammatory molecules TGFβ1, IL-1ra, IL-10 and sTNFR-I/II were significantly elevated in GA compared to OA. CIS and SOCS3 were upregulated in the synovium and SFMCs from acute GA and MSU crystal-stimulated monocyte-derived macrophages and RAW264.7 cells. CIS overexpression in RAW264.7 cells attenuated MSU crystal-induced IL-1β and TNFα but enhanced TGFβ1 production via increased binding of signal transducer and activator of transcription 3 (STAT3) to the TGFβ1 promoter. Conversely, CIS knockdown reversed the effect of CIS overexpression, resulting in enhanced IL-1β and TNFα but reduced TGFβ1 production in MSU crystal-stimulated RAW264.7 cells. Conclusions: Increased production of TGFβ1, IL-1ra, IL-10 and sTNFR-I/II and upregulation of intracellular CIS and SOCS3 expression are associated with spontaneous resolution of acute GA.